2006
DOI: 10.1002/bip.20441
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of β‐turn and Asx‐turns mimicry in a model peptide: Stabilization via CH · · · O interaction

Abstract: The chemical synthesis and single-crystal X-ray diffraction analysis of a model peptide, Boc-Thr-Thr-NH2 (1) comprised of proteinogenic residues bearing an amphiphilic Cbeta -stereogenic center, has been described. Interestingly, the analysis of its molecular structure revealed the existence of a distinct conformation that mimics a typical beta-turn and Asx-turns, i.e., the two Thr residues occupy the left- and right-corner positions. The main-chain torsion angles of the N- and C-terminal residues i.e., semiex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…Thus, the modified sequence 6 , TVPLN, was rationally designed to study the effect of hydrogen bonding and turn conformation on peptide binding and activity. In this case, the rationale for the exchange of the N ‐terminal Thr and Val, and replacement of the C ‐terminal Lys for Asn was based on the short peptide sequences which promoted turn conformations due to stable hydrogen‐bonding interactions with terminal Thr and Asn residues . Moreover, molecular docking studies revealed four H‐bonding interactions in between peptide 6 and the NKp30 binding site residues, Gly51 and Val53 (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the modified sequence 6 , TVPLN, was rationally designed to study the effect of hydrogen bonding and turn conformation on peptide binding and activity. In this case, the rationale for the exchange of the N ‐terminal Thr and Val, and replacement of the C ‐terminal Lys for Asn was based on the short peptide sequences which promoted turn conformations due to stable hydrogen‐bonding interactions with terminal Thr and Asn residues . Moreover, molecular docking studies revealed four H‐bonding interactions in between peptide 6 and the NKp30 binding site residues, Gly51 and Val53 (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…replacement of the C-terminal Lys for Asn was based on the short peptide sequences which promoted turn conformations due to stable hydrogen-bonding interactions with terminal Thr and Asn residues. 41,42 Moreover, molecular docking studies revealed four H-bonding interactions in between peptide 6 and the NKp30 binding site residues, Gly51 and Val53 ( Figure 1). The Gly51 and Val53 residues of NKp30 also contributed in H-bonding of the FG loop residues 125-130 (VTPLK) of B7-H6, found at the B7H6:NKp30 binding interface.…”
mentioning
confidence: 99%
“….O¼ ¼C intramolecular hydrogen-bond. 28,32 In the past, Benedetti and coworkers 38 attempted to feature the importance of U-shaped molecular structures to produce rather predictable supramolecular self-assembly from enantiomeric and diastereomeric correlated peptides Boc-D AaaAaa-OMe, where Aaa may be a Leu, aIle, or Met residue. 38,39 Taken together, these studies tend to point out the propensity(ies) of terminally protected homochiral L,L and heterochiral D,L dipeptides for accommodating diverse biologically relevant folded-unfolded structures 40,41 and probably, their controlled supramolecular self-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26] peptide chain reversal at the C-terminus of helical segments terminating in 'Schellma-motif. 32,33 As one of our series of investigations, we have been involved in designing biologically relevant unusual foldedunfolded structural features in Thr containing homochiral or heterochiral model peptides of the type Boc-Aaa-Thr-OMe, where Aaa may be a proteinogenic or nonproteinogenic a-amino acid. 28,32,[34][35][36][37] We previously reported, using X-ray diffraction analysis and 1 H NMR spectroscopy, the characterization of a novel Asx-turns like motif in terminally blocked homochiral peptides Boc-Thr-Thr-OMe and Boc-Thr-Thr-NH 2 , stabilized by an unconventional main-chain to sidechain C c À ÀH.…”
Section: Introductionmentioning
confidence: 99%
“…The first one includes the C5 conformers [2,17] of CH 3 CONHGlu-CONHCH 3 molecule. The BLYP/6-311++G** calculations have been carried out using the PC version [18] of the GAMESS(US) program package [19].…”
Section: The Secondary-structure Models and Computational Methodsmentioning
confidence: 99%